The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1039/b718950h
|View full text |Cite
|
Sign up to set email alerts
|

Selenoether macrocyclic chemistry—syntheses and properties of new potentially tridentate and hexadentate Se/O-donor macrocycles

Abstract: Treatment of O(CH2CH2SeCN)2 with Na in NH3(l), followed by dropwise addition of a thf solution of o-C6H4(CH2Br)2 at -40 degrees C leads to formation of three mixed Se/O-donor macrocycles which are separable by column chromatography, the [1 + 1] species L1, the [2 + 2] ring L2 and the [3 + 3] ring L3, of which L2 is by far the major species. Using the same starting materials, but in a high dilution cyclisation at room temperature with NaBH4 in thf/EtOH gives exclusively the [1 + 1] ring, L1. The saturated ring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…We have recently utilised a similar strategy for the preparation of a range of small ring selenoether macrocycles. 21,22…”
Section: Ligandsmentioning
confidence: 99%
“…We have recently utilised a similar strategy for the preparation of a range of small ring selenoether macrocycles. 21,22…”
Section: Ligandsmentioning
confidence: 99%
“…A series of Se/O mixed donor macrocycles of varying ring sizes and incorporating ortho xylyl units, such as L 59 , have been synthesised by Reid and co-workers. 85 The smaller ring analogues forms 2:1 complexes copper(I) and silver(I) with two ligands present for each metal ion, however these appeared to be less stable than compounds formed with the larger ring chelators.…”
Section: O- P-and S-donor Macrocyclesmentioning
confidence: 99%
“…[5][6][7][8][9] The development of efficient chemosensors for heavy metal ions with biological and environmental interests is an area of intense activity in order to address practical needs, 10,11 such as Cu 2+ and Hg 2+ because of their bioaccumu-lation and toxicity. 12,13 The soft donor atom Se has been proven to coordinate well with late transition and heavy metal cations, [14][15][16][17][18][19][20][21][22] for example, Singh's group reported that Schiff base macrocycles with Se/Te can be good candidates for heavy metal cation sensing, while there exists a contradiction between stability and coordination of the selenium atoms prevented by larger selena Schiff base macrocycles. 14 Our group has embarked on the systematic study of multichannel probes based on macrocyclic polyselena [n]ferrocenophanes with the target to sense different kinds of metal cations.…”
Section: Introductionmentioning
confidence: 99%